Simulation of impurity behaviour in Experimental Advanced Superconducting Tokamak L‐mode discharges with the integrated COREDIV code. Issue 6 (13th June 2018) - Xie, H.; Zagórski, R.; Ding, R.; Ivanova‐Stanik, I.; Chen, J. L.; Zang, Q.; Duan, Y. M.; Zhang, H. M.; Lyu, B.; Chen, Y. J.; Feng, W.
Abstract : The self‐consistent COREDIV code has been used to simulate the Experimental Advanced Superconducting Tokamak (EAST) L‐mode discharges of upper and lower single null configurations operated with tungsten and carbon divertors, respectively. In the simulations, a uniform lithium injection (and, in addition, a C injection for W divertor) from the wall is assumed, and calculations are performed for different diffusion coefficients in the Scrape‐Off Layer (SOL) region. Simulations demonstrate that, in the case with C target, higher lithium flux leads to lower sputtered carbon flux because of the lower particle flux to divertor due to the plasma dilution by lithium. For the case of tungsten target, lithium has almost no influence on plasma parameters. Carbon seeding first leads to higher W concentrations and then to saturated W afterwards. The effect of a prompt re‐deposition process is moderate due to the self‐regulated increase of plasma temperature at the target through tungsten radiation in the core plasma. The simulations can well reproduce the experimental measurements such as plasma density and temperature profiles in the core region, Z eff, total radiation loss and radiation profiles, and electron density and temperature profiles along divertor target.